Social Media Marketing: The Past, Present and Future - Charunayan Kamath. R; Sivakumar Alur (International Journal of Information Science and Management, 2024)
Social Media Marketing (SMM) has impacted marketing significantly in the past decade. This study uses bibliometric and content analysis to examine academic research on Social Media Marketing (SMM). Focusing on the Scopus database, the research analyzed 899 papers from 2011 to 2021, excluding duplicates. We employed performance analysis, science mapping, and content analysis to understand social media marketing comprehensively. The top journal publishing SMM papers was the Journal of Interactive Marketing, with 6424 citations and 41 articles. The most influential author was Hollebeek L D..Science mapping revealed that ‘"influencer marketing",’ ‘"social media advertising,"’ and ‘"social media"’ are the trending themes in SMM. These themes complement the results found in co-citation clusters. Future research should use new theoretical frameworks like the Consumers Online Brand Related Activities (COBRA) Framework and apply Pierre Bourdieu's social capital theory in the context of SMM. This study offers a comprehensive understanding of social media marketing by visualizing the latest fields of research and trending themes. This study identifies various strategies used in social media marketing and how marketers can garner high engagement. This study utilizes various bibliometric methods to deliver a broad view of social media marketing and content analysis. The latest trends in the field are identified through science mapping techniques. Further, it also gives insight into the top authors and journals that prominently publish literature on social media marketing.